Penyuluhan Pentingnya Pendidikan Seksualitas Anak Usia Dini Bagi Orang Tua sebagai Bentuk Child Safety dan Self Defence Anak - Purnama Dewi, Intan; Pradikto, Bayu; Darmawan, Daddy; Hadiyanti, Puji; Khoiriyah, Fitri; Syifa Nabibah, Asma (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
Concerns about the increasing number of cases of sexual violence against children have recently made parents increasingly worried. Parents' low level of knowledge about the importance of sexuality education and the role of the family as the front line in preventing violence and abuse against children. This community service activity was carried out as an effort to increase parents' understanding of sexuality education for early childhood and school-age children in order to foster child safety and self-defense. The activity was held in Sukaharja Village, Sukamakmur District, Bogor Regency, and was attended by 20 participants, all of whom were mothers with early childhood and elementary school-aged children. The activity was carried out through counseling using an interactive lecture approach, group discussions, and practice/simulations. The results of the activity showed a significant increase in participants' understanding from the low category (45.5 points) to the high category (79.45 points). The activity evaluation showed a level of participant satisfaction in the good to very good category in aspects of the relevance of the material to the participants' needs, clarity and quality of material delivery, counseling methods and techniques, participant involvement and participation, the benefits of the activity for participants, and the completeness of supporting facilities for the activity. Through this activity, participants gained new insights into how to educate children to protect themselves wisely in digital and social environments. This activity demonstrated the community's active involvement in building a culture of safe, educational, and child-protection-oriented parenting.